1992
DOI: 10.1038/bjc.1992.23
|View full text |Cite
|
Sign up to set email alerts
|

Explanation at the opioid receptor level for differing toxicity of morphine and morphine 6-glucuronide

Abstract: Summary The radiolabelled opioid receptor binding affinities of morphine and its active metabolite morphine 6-glucuronide at the total mu, mu 1, mu 2 and delta receptors were determined. Morphine 6-glucuronide was found to have a 4-fold lower affinity for the mu 2 receptor (IC50 17 nm and 82 nm for morphine and morphine 6-glucuronide respectively, P = 0.01), the receptor postulated to be responsible for mediating the respiratory depression and gastrointestinal effects after morphine. This provides a possible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 27 publications
2
23
1
1
Order By: Relevance
“…Such receptors may be involved in the regulation of bladder function, and it may be speculated that the subtype of it receptor involved in spinal and/or supraspinal modulation of bladder motility is different from that involved in somatosensory antinociception. Supporting such a view, Hucks et al (1992) found that M6G had a 4 to 5 fold lower binding affinity for the t2 receptor subtype than morphine. The ,.2 receptor is believed to mediate, e.g., respiratory depression (Ling et al, 1985).…”
Section: Discussionsupporting
confidence: 54%
“…Such receptors may be involved in the regulation of bladder function, and it may be speculated that the subtype of it receptor involved in spinal and/or supraspinal modulation of bladder motility is different from that involved in somatosensory antinociception. Supporting such a view, Hucks et al (1992) found that M6G had a 4 to 5 fold lower binding affinity for the t2 receptor subtype than morphine. The ,.2 receptor is believed to mediate, e.g., respiratory depression (Ling et al, 1985).…”
Section: Discussionsupporting
confidence: 54%
“…[85][86][87][88] In one study, M6G had a fourfold lower affinity for m 2 -receptors than did morphine (IC 50 values of 17 nM (morphine) and 82 nM (M6G)). 72 In this study, there were no significant differences in the receptor binding affinities of morphine and M6G at m 1 -receptors. It was suggested that this differential affinity might explain the lesser effects of M6G compared to morphine on respiratory depression.…”
Section: Receptor Subtypes and Splice Variantsmentioning
confidence: 80%
“…M6G is also more potent than morphine (146 : 1) at producing rewarding e ects measured with place preference testing following intracerebral administration (Abbott & Franklin, 1991). Binding studies show that M6G has an equal or lower a nity for the muopioid receptor than morphine (Abbott & Palmour, 1988;Chen et al, 1991;Hucks et al, 1992;Lambert et al, 1993;Mignat et al, 1995;LoÈ ser et al 1996;Brown et al, 1997b;Pan et al, 1999). In order to explain these di erences in the potencies of M6G and morphine, it has recently been hypothesized that M6G has selective antinociceptive and other behavioural agonist e ects at a receptor that is not activated by morphine (reviewed by Pasternak & Standifer, 1995).…”
Section: Introductionmentioning
confidence: 99%